Gambaran Kompetensi Profesional Tutor Menurut Warga Belajar pada Program Kesetaraan Paket B di PKBM Legusa Kabupaten Lima Puluh Kota - Febri Ramadani; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high attendance of the Paket B equality program and the success of the Paket B education program in PKBM Legusa. This research also purpose to describe the tutor's professional competence in the management aspects of the classroom environment, the use of learning methods, the use of instructional media, and the implementation of learning evaluation. This research use descriptive quantitative approach. For supporting this approach, researcher take 50% of the population is 34 people with a sampling technique that is stratified random sampling. Data collection techniques using questionnaires, and data collection tools using questionnaires. Data analysis techniques use a percentage formula. The results showed that the professional competence of tutors in classroom environmental management aspects was very good, the aspects of using the learning method were very good, the aspects of using the learning media were very good, and the evaluation aspects were very good. For tutors in improving professional competence.Keywords: Competension, Tutor, Equality